Adverse Effects of Treatment with Porcine Factor VIII - Gringeri, A; Santagostino, E; Tradati, F; Giangrande, P LF; Mannucci, P M (Thrombosis and Haemostasis, 1991)
In the last 10 years 63 courses (283 infusions) of porcine FVIII were given to 25 hemophiliacs with high titer alloantibodies and to 5 patients with autoantibodies to factor VIII. Although the product was in general clinically efficacious, adverse effects of treatment were more frequent and severe than previously reported. After 63 courses there was a median percentage fall in baseline platelet count of 54% (range 8-86%); for 10 courses (16%), thrombocytopenia was severe or moderately severe (<100 × 109/1), with nadirs of platelet count ranging from 10 to 99 × 109/1 (median 67). Allergic reactions were seen in 15 of 30 patients (50%), in 20 of 63 courses (32%), more frequently but not exclusively after the first infusion. Relatively mild symptoms (fever, Hushing, urticaria, shivering) occurred in 15 courses; 5 courses, however, were accompanied by more severe anaphylactoid reactions, 2 of which required resuscitation therapy. Allergic reactions were observed both in patients pretreated with steroids or anti-histamines (in 7 of 18 courses, 39%) and in nonpretreated patients (in 13 of 45 courses, 29%). In conclusion, adverse reactions are frequent after porcine FVIII (in 30 of 63 courses, 47%), and can occur also with infusions subsequent to the first. Hence, the recently proposed use of porcine FVIII as home treatment should be implemented with caution.